Aberrant Th2 inflammation drives dysfunction of alveolar macrophages and susceptibility to bacterial pneumonia - Moser, Emily K (Cell Mol Immunol, 2017)
The ubiquitin ligase, Itch, is required to prevent autoinflammatory disease in mice and humans. Itch-deficient mice develop lethal pulmonary inflammation characterized by the production of Th2 cytokines (for example, interleukin-4 (IL-4)); however, the contribution of Itch to immune defense against respiratory pathogens has not been determined. We found that Itch-deficient mice were highly susceptible to intranasal infection with the respiratory pathogen Klebsiella pneumoniae. Infected Itch-deficient mice exhibited increased immune cell infiltration, cytokine levels and bacterial burden in the respiratory tract compared with control mice. However, numbers of resident alveolar macrophages were reduced in the lungs from Itch-deficient mice both before and after infection. High levels of Th2 cytokines in the respiratory tract correlated with deceased alveolar macrophages, and genetic ablation of IL-4 restored alveolar macrophages and host defense to K. pneumoniae in Itch-deficient mice, suggesting that loss of alveolar macrophages occurred as a consequence of Th2 inflammation. Adoptive transfer of Itch(−/−) CD4(+) T cells into Rag(−/−) mice was sufficient to drive reduction in numbers of Itch-replete alveolar macrophages. Finally, we found that Stat6 signaling downstream of the IL-4 receptor directly reduced fitness of alveolar macrophages when these cells were exposed to the Itch(−/−) inflamed respiratory tract. These data suggest that Th2 inflammation directly impairs alveolar macrophage fitness in Itch(−/−) mice, and elucidate a previously unappreciated link between Th2 cells, alveolar macrophages and susceptibility to bacterial infection.